A case of OHVIRA syndrome - Paz-Montañez, John Jamer; Gaitán-Guzmán, Luisa Fernanda; Acosta-Aragón, María Amparo (Universidad y Salud, 2020)
Introduction: The obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) syndrome, also known as the Herlyn-Werner-Wunderlich syndrome, is a rare müllerian anomaly characterized by didelphic uterus, hemivaginal obstruction, and ipsilateral renal anomaly. The incidence of müllerian malformations is 2% - 3%, OHVIRA being the least common of these cases. Objective: To describe an exceptional case of a müllerian disorder. Case presentation: A 14-year-old adolescent with a history of pelvic pain, dysmenorrhea, and recurrent urinary infections. Renal gammagraphy analysis revealed right renal agenesis, and pelvic magnetic resonance imaging showed a didelphic uterus with right hematocolpos. These findings were confirmed by diagnostic laparoscopy. Conclusions: This syndrome is not well known. Renal anegesis, chronic pelvic pain, and menstrual abnormalities in post-pubertal patients must be presumed as indicators of OHVIRA, whose treatment requires a multidisciplinary approach.